PENGARUH STRATEGIC LEADERSHIP TERHADAP COMPETITIVE POSITIONING MELALUI ACCOUNTING INFORMATION SYSTEM TERHADAP PERUSAHAAN NON MANUFAKTUR DI SURABAYA - Betty, Indrasanti (Business Accounting Review, 2015)
This study aimed to examine the affect of Strategic leadership on competitive positioning through accounting information system . The samples and data used in this study were obtained from 44 managers at 4 sectors of non-manufacturing companies in Surabaya by using questionnaires. The sample selection was done by purposive sampling. This hypothesis was tested by using Partial Least Square (PLS) and descriptive analysis. The results showed strategic leadership directly influenced the competitive positioning. Strategic leadership has significant and positive influence to the accounting information system. The affect of accounting information system was positive but not significant on competitive positioning. Accounting information system as intervening variable was unable to strengthen the affect of strategic leadership on competitive positioning in non manufacture companies in Surabaya.